The formation and development of the rheographic method for studying the hemodynamics of eyes with glaucoma - A. P. Kleyman; O. A. Kiseleva; E. N. Iomdina; A. M. Bessmertny; P. V. Luzhnov; D. M. Shamaev (Российский офтальмологический журнал)
Primary or secondary disturbance of blood supply of eye tissues plays a leading role in the pathogenesis of deterioration of visual functions in various ophthalmopathological processes, including primary open angle glaucoma (POAG). For this reason, the study of intraocular hemodynamics can be viewed as a promising direction in clinical ophthalmology. Of particular importance is the evaluation of blood flow in the uveal tract, since it accumulates more than 80 % of blood entering the eye, thus being the primary collector of blood flow and implements the nutritional function in the inner shells of the eye. Rheoophthalmography is one of the main methods of determining the blood supply of the uveal tract. The review presents the evolution of the rheographic method for studying the ocular blood flow since its elaboration in mid-20th century up to the present time // Russian Ophthalmological Journal, 2017; 1: 98-103. doi: 10.21516/2072-0076-2017-10-1-98-103